Multimedia-Assisted Learning in 2D Animation Education - Firman Aziz (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
The advent of the digital era has significantly transformed the educational domain, fostering the incorporation of technology within the learning process to enhance efficacy and foster active participation among students. Innovative learning approaches are necessary to overcome the problems in conventional learning when it comes to 2D animation, which is a valuable asset in education, entertainment, and creative industries. The objective of this study is to create an interactive multimedia platform that can enhance proficiency in 2D animation by employing an educational, captivating, and inspiring design. This study employs the multimedia development life cycle approach to create an interactive educational tool that facilitates students' acquisition of fundamental concepts in 2D animation and the cultivation of practical proficiencies. The findings indicate that the utilization of interactive multimedia holds promise in enhancing students' comprehension of the subject matter, fostering motivation, and cultivating interest in the acquisition of knowledge pertaining to 2D animation. Consequently, this contributes significantly to the realm of contemporary digital education.